Evaluation of tractor traffic on soil physical properties and their relationship with white oat yield in no-tillage - Ale, Larissa Porto; Arcoverde, Sálvio Napoleão Soares; Souza, Cristiano Márcio Alves de; Crestani, Alanda Ferreira; Rafull, Leidy Zulys Leiva (Revista de Ciências Agroveterinárias, 2023)
In a no-tillage system, the absence of soil disturbance combined with increased machine traffic has led to soil compaction in the top layer, negatively affecting its physical quality and hampering crop growth and production. This experiment aimed to assess the impact of tractor traffic, occurring under a no-tillage system, on soil physical properties and their relationship with the growth and yield of white oat crops. The research was conducted in an Oxisol, utilizing a randomized block design with five replications. The treatments consisted of ten consecutive years of no-tillage and additional traffic by 2, 4, 6, and 8 passes of a tractor wheel across the entire plot area. Various soil parameters were evaluated in two soil layers, including soil bulk density, total porosity, macroporosity, and soil resistance to penetration. Additionally, plant height, stem diameter, dry plant mass, mass of one thousand grains, and grain yield were determined. The collected data were analyzed using analysis of variance and linear regression. The results indicated that higher tractor traffic intensity led to increased soil bulk density and reduced macroporosity and soil resistance to penetration in the 0-0.10 m layer compared to the 0.10-0.20 m layer. In the 0-0.10 m layer, bulk density values exceeding 1.44 Mg m-3 were found to restrict the growth and yield of white oat crops, while in the 0.10-0.20 m layer, grain yield was limited when soil bulk density surpassed 1.35 Mg m-3. Our results show that farmers should be aware of the consequences of machine traffic on soil properties as it can have negative effects on crop yields, especially those of white oats grown in clayey soil similar to the one evaluated in this experiment.